Wicked : the life and times of the wicked witch of the West : a novel - Maguire, Gregory (New York : ReganBooks, 2000)
A fable for adults on the subject of destiny and free will by a writer of children's books. It tells the story of Elphaba before she became the Wicked Witch of the West in the land of Oz. The novel traces her career as nun, nurse, pro-democracy activist and animal rights defender.
A fable for adults on the subject of destiny and free will by a writer of children's books. It tells the story of Elphaba before she became the Wicked Witch of the West in the land of Oz. The novel traces her career as a nun, nurse, pro-democracy activist and animal rights defender.
Keywords: Oz (Imaginary place) -- Fiction; Fantasy fiction